Early Miocene (Aquitanian-Burdigalian) Clypeaster and schizaster fauna (Echinoidea: Clypeasteroida, spatangoida) from firat formation, Diyarbakir, southeastern anatolia - Ekin, İhsan (SPRINGER, 2021)
Species belonging to Clypeasteroida and Spatangoida orders are common and abundant in carbonate deposits of the Miocene sedimentary sequences of the Mediterranean region. The current paper deals with the notifying of the Clypeaster and Schizaster fauna (Echinoidea: Clypeasteroida, Spatangoida) from early Miocene (Aquitanian-Burdigalian) of the Firat Formation in Diyarbakir (Egil town), Southeastern Anatolia (Turkey), and their palaeoenvironmental conditions. Eleven specimens have been detected as follows: Clypeaster latirostris (Michelin, 1861) (specimen CLL-1, CLL-2), Clypeaster michelotti (Agassiz, 1840) (specimen CLM), Clypeaster altus (Klein, 1734) (specimen CLA) and Clypeaster intermedius (Des Moulins, 1837) (specimen CLI-1, CLI-2) from Clypeasteroida order, and Schizaster eurynotus (Sismonda, 1841) (specimen SCE-1, SCE-2), Schizaster parkinsoni (Defrance, 1827), (specimen SCP-1, SCP-2) and Schizaster lovisatoi (Cotteau, 1895) (specimen SCL) from Spatangoida order. Southeastern Anatolia consists of soil and rock units (approximately 120,000 km(2)) from the Cambrian to the Miocene. The Miocene sequences of Southeastern Anatolia extend to cermik, Ergani, Dicle, Egil and Hani districts (Diyarbakir) in the north, and Harran (Urfa) and the Syrian border in the south. The article creates an annotated species list with notes on specific aspects of palaeogeographic distribution of Echinoids (Clypeasteroida, Spatangoida) from the early Miocene of Firat Formation in Southeastern Anatolia. Furthermore, since the fossil species identified prefer neritic and sandy-clay habitats, they indicate the tropical climate of the region and become useful for paleoenvironmental reconstructions. Lastly, these data will contribute to providing data for new paleoenvironmental studies by palaeontologists and geologists, and be a pioneer for new fossil records and paleological studies.
Keywords: Clypeaster; Schizaster; Early Miocene; Fırat Formation; Southeastern Anatolia